Unearthing the plant–microbe quid pro quo in root associations with beneficial fungi. Issue 6 (22nd March 2022) - Almario, Juliana; Fabiańska, Izabela; Saridis, Georgios; Bucher, Marcel
Summary: Mutualistic symbiotic associations between multicellular eukaryotes and their microbiota are driven by the exchange of nutrients in a quid pro quo manner. In the widespread arbuscular mycorrhizal (AM) symbiosis involving plant roots and Glomeromycotina fungi, the mycobiont is supplied with carbon through photosynthesis, which in return supplies the host plant with essential minerals such as phosphorus (P). Most terrestrial plants are largely dependent on AM fungi for nutrients, which raises the question of how plants that are unable to form a functional AM sustain their P nutrition. AM nonhost plants can form alternative, evolutionarily younger, mycorrhizal associations such as the ectomycorrhiza, ericoid and orchid mycorrhiza. However, it is unclear how plants such as the Brassicaceae species Arabidopsis thaliana, which do not form known mycorrhizal symbioses, have adapted to the loss of these essential mycorrhizal traits. Isotope tracing experiments with root‐colonizing fungi have revealed the existence of new 'mycorrhizal‐like' fungi capable of transferring nutrients such as nitrogen (N) and P to plants, including Brassicaceae. Here, we provide an overview of the biology of trophic relationships between roots and fungi and how these associations might support plant adaptation to climate change.